Transplantation of adult neural progenitor cells transfected with Vascular Endothelial Growth Factor rescues grafted cells in the rat brain - Maurer, Martin H.; Thomas, Christine; Bürgers, Heinrich; Kuschinsky, Wolfgang (International journal of biological sciences, 2008)
TEST 02 - Elsevier's Scopus, the largest abstract and citation database of peer-reviewed literature. Search and access research from the science, technology, medicine, social sciences and arts and humanities fields.
Gesehen am 13.01.2025